2019
DOI: 10.1371/journal.pone.0213083
|View full text |Cite
|
Sign up to set email alerts
|

Associations between spouses’ oxytocin receptor gene polymorphism, attachment security, and marital satisfaction

Abstract: OXTR rs53576, a polymorphism on the oxytocin receptor gene, has previously been linked to individual differences in social behaviors. That is, individuals with the GG genotype show greater empathy, sociability, and emotional stability. In the context of close relationships, such psychological resources are associated with better relationship outcomes. However, no studies to our knowledge have examined associations between spouses’ OXTR polymorphisms, attachment security, and marital satisfaction. In the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Another paper did not detect any associations between OXTR/rs53576 and insecure adult attachment [87]. In the context of close relationships, individuals with the GG genotype also reported higher marital satisfaction than A carriers [88]. Although there is unanimity in assuming the variation of rs53576 as genetic targets responsible for social functioning and prosocial activity [36,41,89,90], the culture-dependent variation of allelic distributions should not be ignored [91].…”
Section: Discussionmentioning
confidence: 99%
“…Another paper did not detect any associations between OXTR/rs53576 and insecure adult attachment [87]. In the context of close relationships, individuals with the GG genotype also reported higher marital satisfaction than A carriers [88]. Although there is unanimity in assuming the variation of rs53576 as genetic targets responsible for social functioning and prosocial activity [36,41,89,90], the culture-dependent variation of allelic distributions should not be ignored [91].…”
Section: Discussionmentioning
confidence: 99%
“…The specific role of OXTR gene polymorphisms in emotional support seeking, related to social norms and culturally normative behavior, has been discussed in several studies [ 32 – 37 ], with OXTR rs53576 being one of the main focuses of attention. OXTR rs53576 has been related to attachment security and marital satisfaction, and GG carriers rated higher compared A carriers [ 38 ]. Li and colleagues reported a positive association between the rs53576 polymorphism and general sociality and concluded that the G allele homozygotes had higher general sociality than the A allele carriers [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Independent of the reported scores on anxiety and avoidance in adult relationships, A/A homozygotes showed a higher number of followings compared to G-carriers. Previous researches highlighted that OXTR /rs53576 G allele is linked to higher marital satisfaction, support seeking in hostile circumstances, and higher empathy than A-carriers [55] , [96] . Conversely, in a few cases, A/A individuals were found to display increased social attitudes and higher social sensitivity than G-carriers [97] .…”
Section: Discussionmentioning
confidence: 99%